ANALYSIS OF GROUND CABLE LEAKAGE CURRENT OF TRANSFORMER 4 IN NORTH BANDUNG SUBSTATION - Robby Jungjunan; Sandi Ismawan; Muhammad Ikhsan Rabigh Nugraha (Peneliti.net, 2026)
Monitoring leakage current in transformer power cables is crucial to prevent system failures and potentially dangerous electrical accidents. Leakage current in cables can damage equipment, pose a fire risk, and even lead to fatal accidents. One such incident is thermal failure caused by excessive heat in the cable. Leakage current monitoring is performed using an ammeter and thermovision , and the monitoring schedule is carried out weekly. Then, calculations are carried out using the thermal failure method followed by comparing the leakage current through calculations with direct measurements. The study was conducted to compare the measured leakage current values with the leakage current values calculated using the thermal failure calculation method at the North Bandung Substation. From the results of the leakage current calculations through thermal failure calculations and direct measurements, there are differences. The leakage current value closest to the standard value is in phase S4 with a leakage current value of 0.38 A (38% of the standard value and 0.066% of the nominal secondary current value).